Epithelial carbonic anhydrases facilitate P(CO(2)) and pH regulation in rat duodenal mucosa - Mizumori, Misa (Blackwell Science Inc, 2006)
The duodenum is the site of mixing of massive amounts of gastric H(+) with secreted HCO(3)(−), generating CO(2) and H(2)O accompanied by the neutralization of H(+). We examined the role of membrane-bound and soluble carbonic anhydrases (CA) by which H(+) is neutralized, CO(2) is absorbed, and HCO(3)(−) is secreted. Rat duodena were perfused with solutions of different pH and P(CO(2)) with or without a cell-permeant CA inhibitor methazolamide (MTZ) or impermeant CA inhibitors. Flow-through pH and P(CO(2)) electrodes simultaneously measured perfusate and effluent pH and P(CO(2)). High CO(2) (34.7 kPa) perfusion increased net CO(2) loss from the perfusate compared with controls (pH 6.4 saline, P(CO(2)) ≈ 0) accompanied by portal venous (PV) acidification and P(CO(2)) increase. Impermeant CA inhibitors abolished net perfusate CO(2) loss and increased net HCO(3)(−) gain, whereas all CA inhibitors inhibited PV acidification and P(CO(2)) increase. The changes in luminal and PV pH and [CO(2)] were also inhibited by the Na(+)–H(+) exchanger-1 (NHE1) inhibitor dimethylamiloride, but not by the NHE3 inhibitor S3226. Luminal acid decreased total CO(2) output and increased H(+) loss with PV acidification and P(CO(2)) increase, all inhibited by all CA inhibitors. During perfusion of a 30% CO(2) buffer, loss of CO(2) from the lumen was CA dependent as was transepithelial transport of perfused (13)CO(2). H(+) and CO(2) loss from the perfusate were accompanied by increases of PV H(+) and tracer CO(2), but unchanged PV total CO(2), consistent with CA-dependent transmucosal H(+) and CO(2) movement. Inhibition of membrane-bound CAs augments the apparent rate of net basal HCO(3)(−) secretion. Luminal H(+) traverses the apical membrane as CO(2), is converted back to cytosolic H(+), which is extruded via NHE1. Membrane-bound and cytosolic CAs cooperatively facilitate secretion of HCO(3)(−) into the lumen and CO(2) diffusion into duodenal mucosa, serving as important acid–base regulators.